Strengthening Religious Values Based on Youth Organizations to Prevent Devious Behavior of The Young Generation - Saputro, Iwan Hardi; Ruhadi, Ruhadi; Arumsari, Nugraheni; Pramono, Didi; Nafi, Ahmad (Universitas Negeri Semarang, 2023)
The challenges of the young generation today are faced with the age of the younger generation itself, where the age of the younger generation is a transitional age from adolescence to adulthood. At this time, of course, the younger generation does not have mature emotional stability, so they are often trapped in situations that lead to deviant behavior, such as drugs, free sex, brawls and other deviant behavior. One solution that can be offered to prevent deviant behavior is through instilling religious values, so this research is urgent to carry out. The aim of this research is to describe how religious organizations implement the cultivation of religious values in an effort to prevent deviant behavior of the younger generation in Wonosobo Regency. The method used in this research is a qualitative research approach which includes stages. The stages of this research method include: (1) preparation; (2) data collection; (3) data analysis; and (4) reflection. The results of this research were that at the beginning of its formation, activities were carried out including joint learning across classes and departments. Through weekly overnight shifts at group members' homes. During these rotating stays, activities include visiting local ulama to gain knowledge. When you return from the gathering, you can study together using discussion or question and answer methods. The peak activity is the joint prayer (mujahadah) after the tahajud at midnight. Apart from routine activities, this group also organizes incidental activities involving the general public such as halal bihalal, seminars and commemoration of other Islamic holidays. Perhaps it was unique for a group of students of that age to have the courage to organize activities featuring religious and youth figures at sub-district level.